Nrf2 Regulates Anti-Inflammatory A20 Deubiquitinase Induction by LPS in Macrophages in Contextual Manner - Haranatha R. Potteti; Lalith K. Venkareddy; Patrick M. Noone; Aparna Ankireddy; Chandramohan R. Tamatam; Dolly Mehta; Chinnaswamy Tiruppathi; Sekhar P. Reddy (MDPI AG, 2021)
The aberrant regulation of inflammatory gene transcription following oxidant and inflammatory stimuli can culminate in unchecked systemic inflammation leading to organ dysfunction. The Nrf2 transcription factor dampens cellular stress and controls inflammation by upregulating antioxidant gene expression and TNFα-induced Protein 3 (TNFAIP3, aka A20) deubiquitinase by controlling NF-kB signaling dampens tissue inflammation. Here, we report that Nrf2 is required for A20 induction by inflammatory stimuli LPS in monocyte/bone marrow derived macrophages (MDMΦs) but not in lung-macrophages (LDMΦs). LPS-induced A20 expression was significantly lower in Nrf2−/− MDMΦs and was not restored by antioxidant supplementation. Nrf2 deficiency markedly impaired LPS-stimulated A20 mRNA expression Nrf2−/− MDMΦs and ChIP assays showed Nrf2 enrichment at the promoter Nrf2−/− MDMΦs upon LPS stimulation, demonstrating that Nrf2 directly regulates A20 expression. Contrary to MDMΦs, LPS-stimulated A20 expression was not largely impaired in Nrf2−/− LDMΦs ex vivo and in vivo and ChIP assays showed lack of increased Nrf2 binding at the A20 promoter in LDMΦ following LPS treatment. Collectively, these results demonstrate a crucial role for Nrf2 in optimal A20 transcriptional induction in macrophages by endotoxin, and this regulation occurs in a contextual manner.